PENINGKATAN HASIL BELAJAR SISWA PADA KONSEP PENCEMARAN LINGKUNGAN MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) - Juanengsih, Nengsih; Mahmudah, Laelatul; Ruri, Ruri (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to improve the learning outcomes with the use of Project Based Learning (PjBL) model on the concept of environmental pollution. The research method used was Classroom-based Action Research (CAR) with data collection techniques in the form of learning result test, observation sheet, and field notes. This research was a research conducted in two cycles. Each cycle consisted of planning, implementing, observing, and reflecting. The subjects of the study were the students of class X MIPA 1 SMAN 9 Tangerang Selatan in academic year 2016/2017 with the number of students was 38. The research instruments used were test and non-test instrument. Instrument test was in the form of multiple choices (30 questions), while the non-test instruments were in the form of observation sheets and field notes. The data analysis technique was by using N-gain test. The result of this research showed that the improvement of learning outcome in the concept of environmental pollution with the use of learning model based learning (PjBL) in each cycle was 47.37% in the cycle I, and 94.73% in the cycle II. The learning activity of the students showed the increase of activity with the use of learning model Project based learning (PjBL) in the cycle which was 72% in cycle I, and 78% in cycle II. The result of N-gain analysis showed the increase of N-gain from pretest to posttest in which the average of N-gain value in cycle was 0.32 in cycle I and 0.53 in cycle II. Thus it can be concluded that there is influence from the application of the model of Project Based Learning (PjBL) to improve student learning outcomes on the concept of environmental pollution.